Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T16:57:27+02:00
To zadanie można rozwiązać metodą na krzyż:
A)6*(x-4)=7*1,5
6x-24=10,5
6x=10,5+24
6x=34,5 /:6
x=5,75

B) -0,03*(3x-5)=10*6
-0,9x+1,5=60
-0,9x=60-1,5
-0,9x=58,5 /:(-0,9)
x= -65
C)-5*1,4=2*(10-0,75x)
-7=20-1,5x
1,5x=20+7
1,5x=37/:1,5
x=24,(6)
D)2*(4x+5)=-4*(4-3x)
8x+10=-16+12x
8x-12x=-16-10
4x=-26/:4
x=6,5
E) 3*(5-3x)=9*(-2x+7)
15-15x=-18x+63
-15x+18x=63-15
3x=48 /:3
x=16
F)2x*(3x-7)=1,5x*(4x-3)
6xkw.-7x=6xkw.-4,5x
6xkw.-6xkw.-7x+4,5x=0
2,5x=0 /2,5
x=0





5 4 5